Characterization of the child's academic performance in the absence of at least one parent. Case: Milagro City - Liliana Arias Guevara (Pontificia Universidad Católica del Perú, 2013)
I made this research to help children of Milagro City, Ecuador. Here, there is a high proportion of school students without their parents at home. It was possible todefine, by mathematical methods, the typical student's characteristics, his typical family, and a typical situation at classroom according to the reasons of the absence (in a state school or in a private school) and some aspects about his recuperation; however you should not forget that this information is only a reference because each student is a different case to be entirely analyzed. This research could be repeated in other cities.